FROM PERCEPTION TO INTENTION: THE IMPACT OF BRAND IMAGE AND ELECTRONIC WORD OF MOUTH ON BEAUTY CLINIC SELECTION - Cahyani, Syabila Gita Putri; Anwar, Tezza Adriansyah; Samoedra, Artarina Dewi Asri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
The rapid growth of the beauty clinic industry in Indonesia has increased competition among service providers, making it important to identify factors influencing patient intention. This study aims to analyze the effect of brand image and electronic word of mouth (e-WOM) on patient intention to choose the services of Beauty Clinic X. This research uses a quantitative approach with descriptive and verificative methods. Data were collected through questionnaires distributed to 400 respondents using purposive sampling. Data analysis was conducted using validity and reliability tests, correlation analysis, and path analysis with SPSS and LISREL software. The results show that brand image and electronic word of mouth simultaneously have a significant effect on patient intention. Partially, brand image has a positive and significant influence by strengthening trust and reducing perceived risk in choosing beauty clinic services. Electronic word of mouth has a stronger and more dominant effect, indicating that online reviews, recommendations, and shared experiences play a crucial role in shaping patient interest. The findings also reveal that positive brand image and credible e-WOM complement each other in influencing patient decision-making. This study concludes that strengthening brand image and managing credible electronic word of mouth are essential strategies to increase patient intention. Beauty clinics are encouraged to optimize digital marketing efforts, enhance social media engagement, and actively manage online reviews to improve visibility and competitiveness.